VD_FINDINFO HC / 2014 / 494 vom 17. Juni 2014 - VD Tribunal cantonal (2014)
EXPULSION DE LOCATAIRE, PROLONGATION DU DÉLAI, SOMMATION, BAIL À LOYER, DEMEURE DU DÉBITEUR, CAS CLAIR | 257d al. 1 CO, 257d CO, 257 al. 1 CPC (CH), 257 CPC (CH), 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 308 CPC (CH)